Über die Hyperfläche in bilinear-metrischen projektivem Raum - Stiklakytė, L. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Л. Стиклаките. О гиперповерхностях билинейно-метрического проективного пространства L. Stiklakytė. Apie dvitiesiškai-metrinės projektyvinės erdvės hiperpaviršius